Imaging the Role of Inflammation in Mood and Anxiety-related Disorders - Felger, Jennifer C. (Current Neuropharmacology, 2018)
Background: Studies investigating the impact of a variety of inflammatory stimuli on the brain and behavior have reported evidence that inflammation and release of inflammatory cytokines affect circuitry relevant to both reward and threat sensitivity to contribute to behavioral change. Of relevance to mood and anxiety-related disorders, biomarkers of inflammation such as inflammatory cytokines and acute-phase proteins are reliably elevated in a significant proportion of patients with major depressive disorder (MDD), bipolar disorder, anxiety disorders and post-traumatic stress disorder (PTSD). Methods: This review summarized clinical and translational work demonstrating the impact of peripheral inflammation on brain regions and neurotransmitter systems relevant to both reward and threat sensitivity, with a focus on neuroimaging studies involving administration of inflammatory stimuli. Recent translation of these findings to further understand the role of inflammation in mood and anxiety-related disorders is also discussed. Results: Inflammation was consistently found to affect basal ganglia and cortical reward and motor circuits to drive reduced motivation and motor activity, as well as anxiety-related brain regions including amygdala, insula and anterior cingulate cortex, which may result from cytokine effects on monoamines and glutamate. Similar relationships between inflammation and altered neurocircuitry have been observed in MDD patients with increased peripheral inflammatory markers, and such work is on the horizon for anxiety disorders and PTSD. Conclusion: Neuroimaging effects of inflammation on reward and threat circuitry may be used as biomarkers of inflammation for future development of novel therapeutic strategies to better treat mood and anxiety-related disorders in patients with high inflammation.
Keywords: depression